Realising the Public Potential of Corporate Law: Twenty Years of Civil Penalty Enforcement in Australia. (March 2014) - Welsh, Michelle
Traditionally corporate law has been viewed as having characteristics that are commonly associated with private law. Largely this view developed as a result of the "law and economics" scholarship which dominated the corporate law debate, especially in the United States, in the last quarter of last Century. While the traditional "law and economics" approach supports the view that corporate law should be treated as a branch of private law, and that the state should have no role in its enforcement, other scholars, particularly those that adopt a progressive approach, argue that corporate law has, and should be recognised as having characteristics that are usually associated with public law. Arguably, an area of Australian corporate law that displays characteristics that are usually associated with public law is the statutory directors' duties and the civil penalty regime that supports them. This enforcement regime gives the state through the corporate regulator, standing to take court based proceedings to enforce what are in effect, contracts that established corporate governance structures. This article seeks to determine the appropriate role of a public regulator in these circumstances. The questions considered are: whose interests should the public regulator represent when it is tasked with the responsibility of enforcing the statutory directors' duties that largely codify fiduciary and common law duties? Given that the duties are owed by directors to their company should the primary role of the public regulator be to represent the interests of the company, and its shareholders, who have suffered a loss as a result of the alleged contravention of the directors' duties or should the primary role of the public regulator be to act in the interests of the members of the larger community? In these situations what are the interests of the larger community? Drawing on regulatory theory the argument advanced in this paper is that despite the fact that the statutory directors' duties codify what are in effect private rights between directors and their companies, the primary role of a public regulator is not to utilise the enforcement mechanisms at its disposal in order to obtain compensation for companies who have suffered a loss. Rather, the regulator's primary role is to act in the interests of the larger community by utilising the enforcement mechanisms at its disposal strategically in order to encourage greater compliance.